Uncovered power : external agenda setting, sophisticated voting, and transnational lobbying - Silvia Console Battilana (Center for Economic Studies and ifo Institute (CESifo), 2007)
Where does the balance of power lie in a policy-making institution with an external agenda setter, legislators, and lobbies? In a multiple round majority rule game with sophisticated actors, we show that the agenda setter obtains its most preferred policy outcome even if all lobbies and legislators prefer the status quo to the proposal (i.e., the proposal lies in the covered set). A lobby with the ability to recruit supermajorities can counterbalance this power. If contributions are conditional on the entire voting profile, such a 'transnational lobby' can veto any proposal at no cost. If contributions are conditional on the votes of each recipient legislator, the transnational lobby has only to possess a greater willingness to pay than the median national lobby to achieve this result. We use our formal model to explain external tariff policies in the European Union following the creation of an internal market.
Keywords: D02; C7; F1; N54; 330; Politische Entscheidung; Abstimmungsregel; Verhandlungsmacht; Zollpolitik; Public Choice; Interessenpolitik; EU-Binnenmarkt; EU-Staaten